The Oral Health Status and Treatment Needs of Pediatric Patients Living with Autism Spectrum Disorder: A Retrospective Study - Sara Hasell; Ahmed Hussain; Keith Da Silva (Dentistry Journal, 2022)
Background: The objective of this retrospective study was to assess the oral health status and treatment needs of children with ASD and to explore the differences in risk factors and oral health care status and the risk factors for treatment under GA. Methods: Dental charts of children between 6 and 14 years of age who were examined at a dental facility associated with the College of Dentistry, University of Saskatchewan between 2016 to 2019 were assessed. Children who were identified as having ASD, as well as an age- and gender-matched control group consisting of otherwise healthy children were included in the study. Results: The sample included 346 dental records, with 173 children having a diagnosis of ASD. Children diagnosed with ASD had significantly higher experience with caries (91.3% vs. 65.9%, p = 0.003) and severity (mean DMFT/dmft = 8.18 ± 1.62 vs. 4.93 ± 0.58 p = 0.007). Children with ASD were also older when visiting the dentist for the first time (age of 5.97 ± 1.18 vs. 2.79 ± 1.09, p = 0.02)). Children with ASD were less likely to brush once a day (66.5% vs. 88.4%, p = 0.02), were more likely to have bruxism (35.8% vs. 10.4%, p = 0.003) and were less likely to have class I occlusion (64.7% vs. 80.9%, p = 0.03). Findings from the logistic regression analysis revealed that children with ASD were also 2.13 times more likely to receive a referral for general anesthesia when all other variables were held constant (p = 0.03). Conclusions: This research demonstrates that children diagnosed with ASD may face more barriers with access to oral health care, leading to poorer outcomes and greater treatment dental needs.